THE RELATIONSHIP BETWEEN STRESS AND MENSTRUAL CYCLE DISORDERS IN ADOLESCENT WOMEN IN PEMATANG SIANTAR PRIVATE JUNIOR HIGH SCHOOL 2018 - Arsiaty Sumule; Beta Hanindiya; Yulia Delfahedah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Menstruation is a natural process for women, namely the decay of the endometrial wall which comes out through the vagina along with blood, the normal menstrual cycle is 21-35 days. Disorders of the menstrual cycle are influenced by disturbances in hormone function, systemic disorders, stress, thyroid gland, and excessive prolactin hormone. Currently, there are many facts that reveal the relationship between stress and menstruation which is a health problem. The purpose of this study was to determine the relationship between stress and menstrual cycle disorders in young women in private junior high schools. TELADAN Pematangsiantar 2018. The method used is an analytical survey method with a cross sectional approach. The population of this study was all grade 3 students at TELADAN Pematangsiantar Private Middle School as many as 5 million people, the sample technique used was total sampling. The sample in this study amounted to 47 people. Data analysis Univariate analysis was performed to find out the description of the respondents according to the variables studied in the form of a frequency distribution table, while bivariate analysis used the chi-sguare test. Results At the end of the study, it was found that 31 respondents (66.0%) experienced severe stress with details of 18 respondents (58.1%) with normal menstrual cycles and 13 respondents (14.9%) with abnormal menstrual cycles (polymenorrhea). . Value =-0.035(p0.05). The conclusion in this study is that there is a relationship between stress and menstrual cycle disorders with p-0.0.035 (p <0.05). Suggestions for society in general and female students in particular in dealing with stress to make stress as a motivation not as a pressure so that it does not have a bad effect on health,